2023
DOI: 10.3390/robotics12040093
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Heuristic Approaches for Mobile Robot Path Planning: A Survey

Abstract: The most important research area in robotics is navigation algorithms. Robot path planning (RPP) is the process of choosing the best route for a mobile robot to take before it moves. Finding an ideal or nearly ideal path is referred to as “path planning optimization.” Finding the best solution values that satisfy a single or a number of objectives, such as the shortest, smoothest, and safest path, is the goal. The objective of this study is to present an overview of navigation strategies for mobile robots that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…Centralized approaches include such methods as ant colony optimization (ACO), genetic algorithm (GA), and particle swarm optimization (PSO). Ding and Abdulsaheb optimized multiple terrestrial robots using ACO to find a specific target location [20,21]. Majeed exploited the TSP using ACO to find the most efficient traversal of the tour [22].…”
Section: Algorithms Of Uav Cooperative Task Allocation In Disaster Re...mentioning
confidence: 99%
“…Centralized approaches include such methods as ant colony optimization (ACO), genetic algorithm (GA), and particle swarm optimization (PSO). Ding and Abdulsaheb optimized multiple terrestrial robots using ACO to find a specific target location [20,21]. Majeed exploited the TSP using ACO to find the most efficient traversal of the tour [22].…”
Section: Algorithms Of Uav Cooperative Task Allocation In Disaster Re...mentioning
confidence: 99%
“…So, it is suggested that using Genetic Algorithms (GA) [47] [48] will help overcome these limitations. Evolutionary algorithms [49], for instance, provide the advantage of covering a large search field while requiring little memory and CPU power. They have the capacity to adapt to their environment.…”
Section: Robots Routing and Path Planning Literature Reviewmentioning
confidence: 99%
“…Then, local optimization is performed between adjacent key nodes by improving and extending the evaluation function of the traditional dynamic window method (IDWA), which further improves path security and smoothness. An overview of navigation strategies for mobile robots that utilize three classical approaches, roadmap (RM), cell decomposition (CD), and artificial potential fields (APF), in addition to eleven heuristic approaches, including GA, ACO, artificial bee colony (ABC), gray wolf optimization (GWO), etc., which may be used in various environmental situations is presented in [27].…”
Section: Related Workmentioning
confidence: 99%